Hubungan Antara Kecemasan Akademik Dengan Plagiarisme Pada Mahasiswa - Putro, Febri Widiyatmoko; , Dra. Juliani Prasetyaningrum, M.Si (2016)
Among students, plagiarism is still frequently encountered. One of the factors caused this problems is feeling anxiety when dealing with academic tasks. In one semester, a student can gets two or three scientific article, it can be individual or group assignments. Beside that, a final year student also have to create a thesis as a main factor to dedice their graduation. It caused the students' anxiety and under pressure, so it leads them to do plagiarism. Based on the prolems, the researcher do this reseach. The aim of this research are : 1) To know the relationship between academics anxiety and plagiarism on students. 2) To know the level of academics anxiety and plagiarism. 3) To know the constribution of academics anxiety and plagiarism. 4) To know the differences of academics anxiety between man and woman. 5) To know the differences of plagiarism between man and woman. Hypothesis on this research there is positive relationship between academics anxiety and plagiarism on students. Plagiarism done by man is higher than woman. The sampling technique used purposive sampling with the subject of as many as 100 students of the Faculty of Psychology of Muhammadiyah University of Surakarta. Measuring instruments used academics anxiety scale and plagiarism scale. The analysis method used corelation between product moment and t-test. Based on analysis of the correlation coefficient (r) of 0.189 and p = 0.030 (p < 0.05) it means that there is a significant positive relationship between academic anxiety with plagiarism in students. The constribution of academic anxiety against plagiarism by 3.6%. Academic anxiety classified as moderate by the empirical mean of 111.54 and hypothetical mean of 120. While plagiarism is low with an average of 61.25 empirical and hypothetical mean of 72.9. The results of t-test analysis plagiarism variables obtained t value of 2.151 and Sig (2-tailed) p = 0.034 (p < 0.05). This shows that there are significant differences of plagiarism based on gender.Plagiarisme done by man is higher than woman.